Owly & Wormy, friends all aflutter - Runton, Andy (Atheneum Books for Young Readers, 2011)
Good friends Owly and Wormy are disappointed when their new plant attracts fat, green, bug-like things, instead of butterflies, until a metamorphosis occurs.